Clinical risk-scoring algorithm to forecast scrub typhus severity - Sriwongpan P; Krittigamas P; Tantipong H; Patumanond J; Tawichasri C; Namwongprom S (Dove Medical Press, 2013)
Pamornsri Sriwongpan,1,2 Pornsuda Krittigamas,3 Hutsaya Tantipong,4 Jayanton Patumanond,5 Chamaiporn Tawichasri,6 Sirianong Namwongprom1,71Clinical Epidemiology Program, Chiang Mai University, Chiang Mai, Thailand; 2Department of Social Medicine, Chiangrai Prachanukroh Hospital, Chiang Rai, Thailand; 3Department of General Pediatrics, Nakornping Hospital, Chiang Mai, Thailand; 4Department of Medicine, Chonburi Hospital, Chonburi, Thailand; 5Clinical Epidemiology Program, Thammasat University, Bangkok, Thailand; 6Clinical Epidemiology Society at Chiang Mai, Chiang Mai, Thailand; 7Department of Radiology, Chiang Mai University, Chiang Mai, ThailandPurpose: To develop a simple risk-scoring system to forecast scrub typhus severity.Patients and methods: Seven years' retrospective data of patients diagnosed with scrub typhus from two university-affiliated hospitals in the north of Thailand were analyzed. Patients were categorized into three severity groups: nonsevere, severe, and dead. Predictors for severity were analyzed under multivariable ordinal continuation ratio logistic regression. Significant coefficients were transformed into item score and summed to total scores.Results: Predictors of scrub typhus severity were age >15 years, (odds ratio [OR] =4.09), pulse rate >100/minute (OR 3.19), crepitation (OR 2.97), serum aspartate aminotransferase >160 IU/L (OR 2.89), serum albumin ≤3.0 g/dL (OR 4.69), and serum creatinine >1.4 mg/dL (OR 8.19). The scores which ranged from 0 to 16, classified patients into three risk levels: non-severe (score ≤5, n=278, 52.8%), severe (score 6–9, n=143, 27.2%), and fatal (score ≥10, n=105, 20.0%). Exact severity classification was obtained in 68.3% of cases. Underestimations of 5.9% and overestimations of 25.8% were clinically acceptable.Conclusion: The derived scrub typhus severity score classified patients into their severity levels with high levels of prediction, with clinically acceptable under- and overestimations. This classification may assist clinicians in patient prognostication, investigation, and management. The scoring algorithm should be validated by independent data before adoption into routine clinical practice.Keywords: severe scrub typhus, risk-scoring system, clinical prediction rule, prognostic predictors